The Effect of Interactive Videos Enhanced With Pop-up Questions on Teacher Candidates’ Learning Performance in Science - Doğru, M. Said; FATİH, YÜZBAŞIOĞLU; Arpacı, İbrahim (Routledge, 2023)
Background Since the early 20th century, the development and widespread adoption of information technologies have created new opportunities in various aspects of human life, including education. This situation has provided educators with numerous opportunities to develop innovative learning methodologies and environments. Nowadays, interactive videos, commonly used in educational settings, provide students with a self-regulated learning environment where they can access learning materials on-demand. Purpose In this research, our aim was to investigate the impact of interactive videos enriched with pop-up questions on the academic achievements of prospective science teachers. Sample A total of 330 science teacher candidates participated in the study. Study I, conducted to assess teacher candidates’ perceptions, involved 302 participants. Study II, which measured the direct effects of the tests, included 330 participants. Design and Methods The study employed a mixed-method design with a quasi-experimental approach to compare learning outcomes. Results The analysis revealed that the majority of participants expressed that interactive videos significantly contributed to their overall learning. While interactive videos did not have a direct impact on test performance, they were found to have an indirect effect. Conclusion Based on these findings, we concluded that interactive videos with pop-up questions positively influenced learning and are worthy of further exploration in future studies.
Keywords: Digital Learning Tools; Interactive Videos; Pop-up Questions; Science Educatıon